Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 5 - Section 5.2 - Negative Exponents and Scientific Notation - Exercise Set: 62



Work Step by Step

$\Big(\dfrac{r^{-2}s^{-3}}{r^{-4}s^{-3}}\Big)^{-3}$ Evaluate the exponential expression: $\Big(\dfrac{r^{-2}s^{-3}}{r^{-4}s^{-3}}\Big)^{-3}=\dfrac{r^{6}s^{9}}{r^{12}s^{9}}=...$ Evaluate the division and simplify: $...=r^{6-12}s^{9-9}=r^{-6}s^{0}=r^{-6}=\dfrac{1}{r^{6}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.